2012
DOI: 10.1501/ozlegt_0000000165
|View full text |Cite
|
Sign up to set email alerts
|

Zihinsel yetersizlikten etkilenmis öğrencilerin okuma hızının artırılmasında sağaltım paketlerinden etkili olanın belirlenmesi

Abstract: ÖzBu araştırmanın amacı; kısa deneysel analizle, (KDA) AbstractThe purpose of this study was to determine the effectiveness of the combined skill-and performance-based intervention packages on improving reading fluency of students with mental retardation using the Brief Experimental Analysis (BEA) and to test the results of the BEA using extended analysis (EA). Two students with mental retardation participated in the study. The study participants were two girls enrolled in sixth grade inclusive classrooms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Analysis of the studies based on the educational and grade levels attended by the students revealed that seven studies were conducted with primary school students (2nd, 3rd, and 4th grades) (Cora-İnce, 2007;Dağlı-Gökbulut, 2019;Gevrek, 2018;Işıkdoğan, 2009;Özak, 2017;Vural, 2019;. Nine studies involved at the secondary school level (5th, 6th, 7th, and 8th grades; Çetinkaya, 2018;Çetrez-İşcan & Coşkun, 2016;Çınar, 2019;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Kalkan, 2019;Kavan, 2020;Orçan, & Özmen, 2012;Sanır et al, 2020), two studies focused on high school students (Coşgun-Başar, 2019;Özaydın, 2019), and five studies included students from mixed grade levels (Akoğlu & Turan, 2012;Arslan-Soyaltın et al, 2021;Cüre, 2018;Çetrez-Arıcan et al, 2017;Güldenoğlu & Kargın, 2012). Additionally, three studies (Atik-Çatak & Tekinarslan, 2008;Duman & Çifçi-Tekinarslan, 2007;Kayahan, 2011) focused on primary school students aged between 11 and 15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the studies based on the educational and grade levels attended by the students revealed that seven studies were conducted with primary school students (2nd, 3rd, and 4th grades) (Cora-İnce, 2007;Dağlı-Gökbulut, 2019;Gevrek, 2018;Işıkdoğan, 2009;Özak, 2017;Vural, 2019;. Nine studies involved at the secondary school level (5th, 6th, 7th, and 8th grades; Çetinkaya, 2018;Çetrez-İşcan & Coşkun, 2016;Çınar, 2019;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Kalkan, 2019;Kavan, 2020;Orçan, & Özmen, 2012;Sanır et al, 2020), two studies focused on high school students (Coşgun-Başar, 2019;Özaydın, 2019), and five studies included students from mixed grade levels (Akoğlu & Turan, 2012;Arslan-Soyaltın et al, 2021;Cüre, 2018;Çetrez-Arıcan et al, 2017;Güldenoğlu & Kargın, 2012). Additionally, three studies (Atik-Çatak & Tekinarslan, 2008;Duman & Çifçi-Tekinarslan, 2007;Kayahan, 2011) focused on primary school students aged between 11 and 15.…”
Section: Resultsmentioning
confidence: 99%
“…İncelenen çalışmalara öğrencilerin devam ettikleri eğitim kademesi, sınıf düzeyi açısından bakıldığında yedi çalışmanın ilkokul (2, 3 ve 4. sınıf) kademesine devam eden öğrencilerle (Cora-İnce, 2007;Dağlı-Gökbulut, 2019;Gevrek, 2018;Işıkdoğan, 2009;Özak, 2017;Vural, 2019;Yüksel, 2019); dokuz çalışmanın ortaokul (5, 6, 7 ve 8. sınıf) kademesine devam eden öğrencilerle (Çetinkaya, 2018;Çetrez-İşcan & Coşkun, 2016;Çınar, 2019;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Kalkan, 2019;Kavan, 2020;Orçan, & Özmen, 2012;Sanır vd., 2020); iki çalışmanın lise kademesine devam eden öğrencilerle (Coşgun-Başar, 2019;Özaydın, 2019) ve beş çalışmanın da karma sınıf düzeylerinden oluşan öğrencilerle (Akoğlu & Turan, 2012;Arslan-Soyaltın vd., 2021;Cüre, 2018;Çetrez-Arıcan vd., 2017;Güldenoğlu & Kargın, 2012) Çalışmaların Gerçekleştirildiği Ortam. İncelenen çalışmaların katılımcı profiline bakıldığında 12 çalışmanın kaynaştırma sınıfına devam eden öğrencilerle (Akoğlu & Turan, 2012;Atik-Çatak & Tekinarslan, 2008;Çınar, 2019;Dağlı-Gökbulut, 2020;Doğanay-Bilgi & Özmen, 2014;Güler, 2008;Güldenoğlu & Kargın, 2012;Işıkdoğan, 2009;Kalkan, 2009;Orçan & Özmen, 2012;Vural, 2019;Yüksel, 2019) yürütülmüş olduğu görülmüştür. Bu çalışmalardan ikisinin (Güler, 2008;Kalkan, 2009) hem kaynaştırma hem de özel eğitim sınıfına deva...…”
Section: Araştırmaların Katılımcı öZellikleriunclassified